Metacognitive Strategies and Reading Development in Islamic Higher Education - Adisaturrahimi, Andi; Suparto, Windy Puspitasari; Marlia, Marlia; Mustaqimah, Mustaqimah; Resyadi, Herman (AT-TA'LIM, 2026)
This study aims to examine the impact of metacognitive strategy instruction on the development of reading skills among undergraduate students at an Islamic higher education. The research focuses on how these strategies influence students’ knowledge, skills, attitudes, and behaviors in reading academic texts. A qualitative descriptive design with a phenomenological approach was employed to explore students lived experiences. Eighteen fourth semester students who had completed a reading course incorporating metacognitive strategies were selected through purposive sampling. Data were collected through semi structured interviews and analyzed using thematic analysis to identify recurring patterns and themes. The findings reveal that metacognitive instruction significantly improved students’ understanding of reading as an active and strategic process. Students demonstrated enhanced skills in monitoring comprehension, questioning, and drawing conclusions. In addition, they reported increased motivation, confidence, and classroom participation. The study concludes that integrating metacognitive strategies into reading instruction fosters self-regulated, reflective, and engaged learners. These results suggest that metacognitive instruction is effective in strengthening both cognitive and affective aspects of reading development in Islamic higher education contexts.